P094: Meeting patient expectations in the emergency department: preliminary findings from the preparing emergency patients and providers study. (15th May 2017) - Nunn, J.; Cassidy, C.; Chiasson, D.; MacPhee, S.; Curran, J.
Abstract : Introduction: Effective communication to develop a shared understanding of patient expectations is critical in establishing a positive medical encounter in the emergency department (ED). However, there is limited research examining patient/caregiver expectations in the ED, and their impact on the beliefs, attitudes and behaviours during and after an ED visit. The objective of this study is to examine patient/caregiver expectations and satisfaction with care in the ED using a patient expectation questionnaire and a follow up survey.Methods: As a part of a larger 3-phase study on patient/caregiver expectations in adult and pediatric EDs, a 7-item, paper-based questionnaire was distributed to all patients and/or caregivers who presented to one of four EDs in Nova Scotia with a Canadian Triage and Acuity Scale (CTAS) score of 2 to 5. A follow-up survey was distributed to all willing participants via email to determine their satisfaction with care received in ED. Descriptive statistics were used to analyze responses.Results: Phase 1 was conducted from January to September 2016. In total, 24, 788 expectation questionnaires were distributed to ED patients/caregivers, 11, 571 were collected (47% response rate), and 509 patients were contacted for a follow-up survey. Preliminary analysis of 4, 533 questionnaires shows the majority of patients (67.1%) made the decision by themselves to present to the ED, while others were advised by a family/friend (22%). Respondents were most worried about an injury (17.8%) followed by illness (15.6%) and expected to talk to a physician (69.9%) and receive an x-ray (39.3%). The majority of physicians (53.3%) reported the expectation tool helped in caring for the patient and 87.5% felt they met patient expectations. There were 147 patient/caregiver responses to a follow-up survey (29% response rate) and 87.1% of responders reported that ED clinicians met their expectations.Conclusion: Patient/caregivers have a variety of concerns, questions, and expectations when presenting to the ED. Obtaining expectations early in the patient encounter may provide opportunities for improved communication between clinicians and patients while enhancing satisfaction with care received. Further analysis is needed to determine the impact of the expectation questionnaire on productivity in the ED.